Effects of Reducing the South and Reinforcing the North Method on Inflammatory Injury Induced by Hyperlipidemia. (21st September 2021) - Wu, Hongjin; Dai, Weiwei; Wang, Libo; Zhang, Jie; Wang, Chenglong
Abstract : Inflammation is the pathophysiological basis of hyperlipidemia-related disease (HRD). Reducing the south and reinforcing the north method (RSRN) has a positive effect on HRD. However, the pharmacological mechanisms of RSRN are still unclear in the treatment of HRD. We obtained RSRN compounds from the Traditional Chinese Medicine Systems Pharmacology (TCMSP) and identified potential targets of these compounds through target fishing based on the TCMSP databases. Next, we identified the HRD targets by using multiple databases. Then, the overlapping genes between the RSRN potential targets and the HRD targets were used to establish a protein-protein interaction (PPI) network, and we further analyzed their interactions and identified the major hub genes in this network. Subsequently, the Metascape database was utilized to conduct the enrichment of Gene Ontology biological processes (GO) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathways. A total of 187 potential active components and 106 related core targets were obtained and identified overall. Then after the Metascape enrichment analysis, a total of 148 KEGG pathways were screened, which were mainly associated with AGE-RAGE signaling pathway, PI3K-Akt signaling pathway, TNF signaling pathway, and NF-kappa B signaling pathway. Furthermore, 34 hub genes, such as AKT1, NF- κ Bp65(RELA), I κ B α (CHUK), MAPK8, and MAPK14, CCND1, were considered potential therapeutic targets. Furthermore, evaluations of protein levels of NF- κ Bp65, I κ B α, TNF- α, IL-1 ß, and IL-6 were performed for experimental validation. RSRN can reduce the expression of NF- κ Bp65 protein, increase the level of I κ B α protein, and reduce the protein levels of TNF- α, IL-1 β, and IL-6 in ovariectomized rats. The results indicate that the mechanism of RSRN against inflammation may be related to AKT1, NF- κ Bp65, I κ B α, MAPK8, and MAPK14, as well as TNF, NF-kappa B, PI3K-Akt signaling pathways.